Peculiarities of Intersystemic Correlation Relationships of M-Response and F-Wave Characteristics in the Forearms Symmetric Muscles Which Participate in the Implementation of Multiple Coordinated Bimanual Movements - Mashoshina, Lada O. (2021)
The organization of combined voluntary goal directed movements of hands has remained a serious scientific problem with a pronounced applicable nature.  Insufficiency of a procedural framework and clear quantitative and qualitative criteria causes gaps and difficulties in professional selection, the effectiveness diagnosis of work-out session in sports and rehabilitation within remedial treatment.  The aim of the investigation is to study the adjustment and co-adjustment of the effector apparatus elements, which are the basis of bimanual coordination, in the groups of male and female trial subjects. In the following study, based on informed consent in accordance with the ethics committee requirements, 75 subjects (39 men and 36 women) at the age of 18-20 took part. F-wave and M-response parameters registration was carried out by means of NMA-4-01 “NEUROMIAN” neuromyoanalyzer (Taganrog, Russia) according to the standard method. It has been established that the nerve centers responsible for the work of homonymous muscles in the right and left forearms, innervating synergists and antagonists, are to a certain extent in the initial adjustment and co-adjustment according to the level of activity, which determines not only the moment of the excitement onset, but also the speed of its irradiation.  The revealed manifestations of adjustment and co-adjustment have pronounced sex differences.  Proceeding from the fact that female trial subjects have a lower level of bimanual movements if compared with men, it can be assumed that the revealed features of correlational relationships determine, to a certain extent, coordination abilities of men and women.